THORACOLUMBAR BURST FRACTURE: LOAD SHARING CLASSIFICATION AND POSTERIOR INSTRUMENTATION FAILURE - Avanzi, Osmar (Elsevier, 2015)
Objectives: To assess the relationship between sagittal collapse, posterior instrumentation failure and the McCormack classification among patients with thoracolumbar burst fractures who had undergone posterior arthrodesis more than one level above and one level below the fracture. Methods: This was a retrospective review based on the medical records and radiographs of 26 patients who underwent operations between January 1990 and December 2006. The parameters assessed were: worsening of kyphosis (Cobb), neurological dysfunction (Frankel) and failure of surgical treatment (implant breakage or loosening). Results: No relationship was found between sagittal collapse and the scoring in the McCormack classification (r = 0.221; P = 0.322). There was also no relationship between failure of the posterior implant and the scoring in this classification (p = 0.85). Conclusion: Our findings suggest that this classification is not applicable to patients who underwent arthrodesis more than one level above and one level below the fracture.